Rancang Bangun Sistem Smart Trafic Light Deteksi Suara Sirine Kendaraan Darurat Metode DTW Studi Kasus: Sirine Pemadam Kebakaran - Maharani, Jinoli Dyahayu; Nurraharjo, Eddy (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The progress of the times demands the active participation of all societal layers in the stream of technological advancements. This progress has given rise to the concept of a Smart City System. One manifestation of this smart city concept is the emergence of intelligent traffic light systems, often equipped with various sensors, including sound sensors. The use of sound sensors allows for the detection of emergency vehicle sirens. Among emergency vehicles, firefighting vehicles should be given the highest priority on the road. Based on this, the researchers developed a system using an Arduino UNO device. This system compares sirens' sounds with other noises and processes them to execute commands on the Arduino UNO. The utilization of the Mel-Frequency Cepstrum Coefficients (MFCC) and Dynamic Time Warping (DTW) algorithms as supporting decision-making components in the system has resulted in a recognition accuracy rate of 70%.